Evaluation of wood quality of selected tropical pines raised in the high ranges of kerala, for pulp and paper making - Ajayghosh V; Anoop E.V(Guide) (Vellanikkara Department of Tree Physiology and Breeding,College of forestry, 2010)
A study entitled (3z(BEvaluation of wood quality of selected tropical pines raised in the high ranges of Kerala, for pulp and paper making(3y (Bwas conducted in the College of Forestry, Kerala Agricultural University, Vellanikkara, Thrissur during the period 2008-2010. The objective of the study was to evaluate the wood quality of Pinus caribaea Morelet, Pinus patula Schl. et Cham. and Pinus oocarpa Schiede grown in research trials of the Kerala forest department in the high ranges of Idukki district of Kerala. Increment core wood samples were collected at breast height from trees, selected at random, from each plot representing each species belonging to different age levels. These samples were then subjected to intensive investigations to find out radial variation (pith, middle and periphery), species variation and influence of age on different wood physical, anatomical and chemical properties. The study revealed that many of the characters studied were influenced by species and age interaction. Radial variation was also found to have significant difference within the species for characters studied. As a whole, under the present climatic condition P.caribaea was found to perform better with wood properties within the accepted range suitable for pulping and paper making. On the other hand, P. patula and P. oocarpa were also found to be promising species for pulping and papermaking with better derived fiber ratios. However, P. oocarpa had specific gravity value slightly more than that is recommended for pulp and paper making. Studies on chemical composition revealed that P. ooccarpa had better performance with higher cellulose and lower lignin content. So what needs to be determined is the relationship, if any, between wood and tracheid properties of these species and the products which can be manufactured from this renewable resource. For this, more extensive study is needed for which the results of this study could be used as a base line data for future tree improvement aspects of these species with reference to wood quality and to bring out their potential utility for future afforestation programmes and timber utility.s